Bioleaching of Iron and Zinc from a galvanized steel waste from automotive industry using Acidithiobacillus thiooxidans: a case of study of the bajío area in México (Nexo Revista Científica, 2023)
Biohydrometallurgy has been defined as a collection of techniques that involve the use of microbial metabolisms, such as the bacterium Acidithiobacillus thiooxidans, for the extraction of metals.  Therefore, in the current study, we tested the potential of a pure culture of A. Thiooxidans in the removal of zinc and iron from galvanized waste of the automotive industry. Starkey medium was employed and was added 0.5% w/v of solid sample, and incubation took place at 30°C, and 180 rpm for 7 days. The experiment showed a biological removal of 100% of Fe and Zn after 72 hours, as shown with the measurements taken using inductively coupled plasma spectrophotometer (ICP-OES). Additionally, an increase of the concentration of sulphates is reported alongside the process. The present study thus suggests that a fast, efficient, and low energy biological process for the recovery of these metals coming from galvanized steel waste is possible.